PERAN INTERNATIONAL COMMITTEE OF THE RED CROSS (ICRC) DALAM MENANGANI KRISIS KEMANUSIAAN DI SUDAN SELATAN TAHUN 2016-2019 - Satri Syafira; Mhd. Saeri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT This research analyzes how the ICRC's role in handling humanitarian crises that occurred due to civil conflict in South Sudan. The civil conflict occurred after South Sudan's independence in 2011, which then triggered the upheaval of armed conflict. This indicated a serious humanitarian crisis due to the conflict. Despite the establishment of a peace agreement in 2015, civil conflict still continues across the country targeting civilians. The ICRC as an organization engaged in the humanitarian field took a big part in handling the humanitarian crisis in South Sudan, until it formed the South Sudan Red Cross after its independence in 2011. The ICRC carries out its humanitarian mission through several programs which then have a significant impact in dealing with the humanitarian crisis there. This research uses a qualitative method, with data collection techniques through literature studies and document analysis from several books, journals, articles, annual reports, and websites with a group level of analysis. This research utilizes Constructivism perspective and Humanitarian Diplomacy theory. The results of this paper indicate that in handling the humanitarian crisis in South Sudan, the ICRC maintains stability and effectiveness in carrying out its humanitarian mission. This can be seen from the achievements made by the ICRC in the span of 2016-2019 which based on its annual report reached a high effective level. Keywords: Civil Conflict, Humanitarian Crisis, ICRC, Humanitarian Diplomacy.